Virtual and augmented reality: potential applications in radiology. (September 2020) - Elsayed, Mohammad; Kadom, Nadja; Ghobadi, Comeron; Strauss, Benjamin; Al Dandan, Omran; Aggarwal, Abhimanyu; Anzai, Yoshimi; Griffith, Brent; Lazarow, Frances; Straus, Christopher M; Safdar, Nabile M
The modern-day radiologist must be adept at image interpretation, and the one who most successfully leverages new technologies may provide the highest value to patients, clinicians, and trainees. Applications of virtual reality (VR) and augmented reality (AR) have the potential to revolutionize how imaging information is applied in clinical practice and how radiologists practice. This review provides an overview of VR and AR, highlights current applications, future developments, and limitations hindering adoption.